2021
DOI: 10.3389/fonc.2021.712807
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Versican as a Potential Immunotherapeutic Strategy in the Treatment of Cancer

Abstract: A growing body of literature links events associated with the progression and severity of immunity and inflammatory disease with the composition of the tissue extracellular matrix as defined by the matrisome. One protein in the matrisome that is common to many inflammatory diseases is the large proteoglycan versican, whose varied function is achieved through multiple isoforms and post-translational modifications of glycosaminoglycan structures. In cancer, increased levels of versican are associated with immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 110 publications
(152 reference statements)
2
8
0
Order By: Relevance
“…Both ITGB4 and VCAN are considered to correlate with ECM and promote tumor invasion and metastasis of breast cancer with elevated expression (38,40). Besides, VCAN also correlated strongly with immune suppression and may be responsible for immunotherapy failure (41), which is in line with the suppressed immune response of ACC in our data. DPT (dermatopontin) is a tyrosine-rich ECM protein, which principally takes a significant role in focal adhesion, matrix remodeling, and metastasis of cancer cells (42).…”
Section: Discussionsupporting
confidence: 89%
“…Both ITGB4 and VCAN are considered to correlate with ECM and promote tumor invasion and metastasis of breast cancer with elevated expression (38,40). Besides, VCAN also correlated strongly with immune suppression and may be responsible for immunotherapy failure (41), which is in line with the suppressed immune response of ACC in our data. DPT (dermatopontin) is a tyrosine-rich ECM protein, which principally takes a significant role in focal adhesion, matrix remodeling, and metastasis of cancer cells (42).…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, our study demonstrates a correlation between the infiltration of CD8+ T cells and favorable prognosis in DLBCL. Here, we propose a hypothesis that in our study, the observed high expression of VCAN might create a suppressive environment for PD-1+ CD8+ T cells [21,38]. Intriguingly, our study revealed a statistically significant correlation between VCAN expression, C1QB expression and CD8+ T cell infiltration.…”
Section: Discussionsupporting
confidence: 63%
“…In our previous work, we identified a specific tumor ECM signature that associated with disease progression and immunosuppression, identified in high-grade serous ovarian cancer (HGSOC) 1 , and shared by 12 other solid carcinomas, including those with limited treatment options such as pancreatic, lung, and esophageal cancers. This ECM signature associated with immunosuppressive cell phenotypes, but did not positively correlate with cytotoxic immune cell phenotypes, and negatively correlated with CD8 T cells 9 . Building on these studies, we applied computational algorithms CIBERSORTx and xCell to these previously gathered datasets 1 to further look at how specific ECM molecules associate with immune cell infiltrate.…”
Section: Introductionmentioning
confidence: 82%